Behavior of pregnant women to improve oral health knowledge during pregnancy according to Lawrence Green theory in Pakis Public Health Service Area - Setyowati, Dini; Nurrahmania, Alfina Putri; Ummah, Nur Imamatul; Prasasti, Aulia Rifda; Aditya, Candra; Rahmi, Zalfa Alifia; Apriliani, Riski Rossa; Hemadi, Abdullah Sherf; Kamila, Nurul Naswaa; Ulhaq, Aqila Dhiya (Indonesian Journal of Dental Medicine, 2024)
Background: Pregnancy involves conception, fetal development, and labor. The health of pregnant women needs to pay attention to aspects of oral health because it affects fetal development. The prevalence of periodontal disease in pregnant women reached 35%-100%. Lawrence Green categorizes behavioral influence factors into two, namely behavior and non-behavior, with three main factors: predisposing, reinforcing, and enabling. Purpose: To determine the relationship between the behavior of pregnant women in increasing knowledge about oral health during pregnancy. Methods: This study used qualitative research methods, and information retrieval using in-depth interviews with research samples, who were pregnant women at Pakis public health service area on September 14-30, 2020. Results: There are main findings found such as, there are still pregnant women who do not know how to maintain oral health during pregnancy, pregnant women still do not try to find out information related to oral health during pregnancy, and it was also found that the information provided at services related to oral health during pregnancy was felt to be lacking by some informants. Conclusion: In terms of knowledge and attitudes (predisposing factors), as well as access to services (enabling factors), informants did not experience any obstacles. In terms of support (reinforcing factors), most informants highlighted the importance of support from husbands, family, relatives, and friends for the oral health of pregnant women.